Leadership Implementation Analysis As Brand Image in Military Organizations: Evidence from Indonesia - Purnomo, Kristanto Setio Hari; Saputra, Andi Wahyu (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2022)
This study seeks to understand and explore field leadership as a brand image in military organizations by analyzing the experiences and perceptions of senior military personnel who have experienced military officers who have led teams, units or combat units. This type of research is descriptive qualitative research with an exploratory study approach. All data collected in this study were obtained by conducting interviews, supported by the experience of researchers and direct observation at the military command headquarters and strengthened by limited and confidential published military literature studies. The results of this study indicate that the implementation of field leadership as a brand image at Kodim 0732/Sleman identified through its indicator aspects has been well implemented. This explains that good military leadership is able to represent the brand image of the organization. Leaders who care and leaders who promote exemplary are the keywords for the success of every military officer in successfully forming a positive brand image both individually and organizationally within the Indonesian National Armed Forces.